Clinical Applications for Diffusion MRI in Radiotherapy - Tsien, Christina (2014)
In this article, we review the clinical applications of diffusion MR imaging in the radiotherapy treatment of several key clinical sites, including those of the CNS, the head and neck, the prostate and cervix. Diffusion-weighted MRI (DWI) is an imaging technique that is rapidly gaining widespread acceptance due to its ease and wide availability. DWI measures the mobility of water within tissue at the cellular level without the need of any exogenous contrast agent. For radiotherapy treatment planning, DWI improves upon conventional imaging techniques, by better characterization of tumor tissue properties required for tumor grading, diagnosis and target volume delineation. Because diffusion weighted MRI is also a sensitive marker for alterations in tumor cellularity, it has potential clinical applications in the early assessment of treatment response following radiation therapy.